Objek Penelitian (Body Of Knowledge) Manajemen Pendidikan Islam - Misda Ariyani; Dina Hermina; Salamah (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study aims to analyse and explain the objects of study in Islamic education management, which include formal objects, material objects, and the research context as part of the body of knowledge. This study employs a qualitative approach in the form of library research, involving a review of various relevant sources of literature on the subject of Islamic education management. Data analysis employs content analysis through the stages of data condensation, data display, and conclusion drawing/verification. The findings indicate that the research objects in Islamic education management are not only related to the aspects under investigation (material objects) but also encompass analytical perspectives or approaches (formal objects) as well as the research context underpinning a study. The material object encompasses various fields of educational management such as leadership, curriculum, learners, personnel, facilities and infrastructure, finance, school-community relations, and educational administration. The formal object is management science (science of management) as the primary perspective, which is then enriched with Islamic values and principles in its application within Islamic educational institutions. Meanwhile, the research context explains the situational background and underlying issues of the study. These findings indicate that clarity regarding the research object is a crucial foundation for establishing a systematic body of knowledge, avoiding overlapping studies, and strengthening the academic identity of Islamic educational management as an independent and focused discipline. Keywords : Research Object, Body of Knowledge, Islamic Educational Management Abstrak Penelitian ini bertujuan untuk menganalisis dan menjelaskan objek penelitian dalam manajemen pendidikan Islam yang meliputi objek formal, objek material, dan konteks penelitian sebagai bagian dari body of knowledge. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian studi pustaka (library research) melalui penelaahan berbagai sumber literatur yang relevan dengan objek penelitian manajemen pendidikan Islam. Teknik analisis data menggunakan analisis isi (content analysis) dengan tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil kajian menunjukkan bahwa objek penelitian dalam manajemen pendidikan Islam tidak hanya berkaitan dengan aspek yang diteliti (objek material), tetapi juga mencakup sudut pandang atau pendekatan analisis (objek formal) serta konteks penelitian yang melatarbelakangi suatu kajian. Objek material meliputi berbagai bidang pengelolaan pendidikan seperti kepemimpinan, kurikulum, peserta didik, personalia, sarana dan prasarana, keuangan, hubungan sekolah dengan masyarakat, serta tata laksana pendidikan. Objek formal manajemen pendidikan Islam adalah ilmu manajemen itu sendiri (management science), yang dalam penerapannya pada lembaga pendidikan Islam diperkaya dengan nilai dan prinsip Islam. Sedangkan konteks penelitian menjelaskan latar situasi dan permasalahan yang mendasari penelitian. Temuan ini menunjukkan bahwa kejelasan objek penelitian menjadi dasar penting dalam membangun struktur keilmuan yang sistematis, menghindari tumpang tindih kajian, serta memperkuat identitas akademik manajemen pendidikan Islam sebagai disiplin ilmu yang mandiri dan terarah. Kata Kunci : Objek Penelitian, Body of Knowledge, Manajemen Pendidikan Islam